2012
DOI: 10.1021/jp2103353
|View full text |Cite
|
Sign up to set email alerts
|

12-Hydroxy-1-azaperylene—Limiting Case of the ESIPT System: Enol–Keto Tautomerization in S0 and S1 States

Abstract: Absorption, fluorescence, and fluorescence excitation spectra of 12-hydroxy-1-azaperylene (HAP) and 1-azaperylene were studied in n-alkane matrices at 5 K. Two stable tautomers of HAP, each of them in n-nonane embedded in two sites, were identified and attributed to the enol and keto forms. Theoretical calculations of the energy and vibrational structure of the spectra suggest that tautomer A, with the (0, 0) transition energy at 18,980 ± 10 cm(-1) (and 19,060 ± 10 cm(-1) in the high energy site), should be id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 59 publications
2
17
0
Order By: Relevance
“…HBQs seems a very good group to study some of the abovementioned phenomena and also to establish whether these compounds are tautomeric or not, considering that 12-hydroxy-1-azaperylene, a close analogue, has been found to be tautomeric [19,20,21]. …”
Section: Introductionmentioning
confidence: 99%
“…HBQs seems a very good group to study some of the abovementioned phenomena and also to establish whether these compounds are tautomeric or not, considering that 12-hydroxy-1-azaperylene, a close analogue, has been found to be tautomeric [19,20,21]. …”
Section: Introductionmentioning
confidence: 99%
“…Excited state inter- and intramolecular proton transfer (ESIPT) has emerged as an interesting phenomenon that can be utilized in the design of fluorescent sensors. Compounds displaying ESIPT include benzoxazoles, flavones, imidazoles, imidazo[1,2- a ]pyridines, and anthraquinones. The photophysical characteristics of ESIPT-capable compounds make them excellent candidates for applications in such diverse areas as laser dyes, , fluorescence recording, , ultraviolet stabilizers, probes for solvation dynamics, probes for biological environments, and recently, organic light emitting devices. , Although 10-hydroxybenzo[ h ]quinoline (HBQ) represents one of the fundamental heterocyclic systems, in which ESIPT occurs, it was only in 1992 when the fundamental studies of Martinez, Chou, and colleagues identified ESIPT as the process responsible for the strongly bathochromically shifted fluorescence of HBQ. , Detailed photophysical and theoretical studies of HBQ showed very fast and solvent-independent ESIPT, and recently more elaborated derivatives were also investigated. …”
Section: Introductionmentioning
confidence: 99%
“…In the excited state the proton may be transferred from amine group (NH) to keto group (C=O) through ESIPT process leads to the existence of both KHB and EHB forms [18][19][20][21][22][23]33]. In dual emission, the low intensity peak at 410 nm arises from the normal ketamine form and the red shifted high intensity peak at 435 nm corresponds to the stable tautomeric enolimine form.…”
Section: Electronic Emission Spectramentioning
confidence: 99%
“…This hypothesis leads to the concept of twisted intramolecular charge transfer (TICT) process. A number of reports have shown that the degree of steric hindrance plays an important role in dual emission arises from twisted intramolecular charge transfer (TICT) or excited state intramolecular proton transfer (ESIPT) process [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%